15 seconds - Gross, Andrew, 1952- (HarperCollins Publishers, 2012)
When a random act of violence plunges him into a nightmarish world, Henry Steadman, a successful surgeon accused of murdering two people, must clear his name and discover who is trying to destroy him in order to save himself and his family.